Leopold's maneuvers - Davis, Cortney, 1945- (Prairie schooner book prize in poetry., 2004)
In the venerable tradition of caregivers writing about the healing arts-a tradition peopled by the likes of Anton Chekhov, Walt Whitman, William Carlos Williams, Walker Percy, and Denise Levertov-Cortney Davis brings to poetry the experience, insight, and compassion of a nurse practitioner who daily confronts the unexpected frailties, passions, and power of the flesh. Taking the body as her text, Davis crafts her poetry from the pains of labor and the joys of birth, the depredations of disease and the sustaining hope of recovery. She trains her clear, unflinching gaze on the unfolding scene-a.